Appendix 4.19: Superexecutive, Supercourt, Superlegislature, and One-Man Constitutional Convention - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
Together, these three laws show (a) that Marcos can overrule Congress/the Batasang Pambansa, not only by vetoing their issuances, but outright amending enacted laws via presidential decree, and (b) that Marcos retained his legislative powers even after convening a legislature and “lifting” martial law due to amendment number 6 of the 1973 Constitution. In effect, he was a one-man upper chamber above a unicameral legislature, even after “normalization.” These laws are also highlighted because of the possible personal reasons behind one’s supersession of the other. As numerous diary entries and news articles show, Marcos was an avid water skier. Section 2(f) of Batasang Pambansa 33 explicilty bans water skiing. Presidential Decree 1688-A’s sole purpose is to modify Batasang Pambansa 33 to allow waterskiing “provided methanol is used for the power fuel.” Among numerous other amendments, Presidential Decree 1865 reiterates that water skiing is allowable when “methanol is used in the power-boat operation.”